Hepatoprotective and anti-oxidant effect of Carissa spinarum root extract against CCl4 and paracetamol-induced hepatic damage in rats - Hegde, Karunakar; Joshi, Arun B. (Bangladesh Journal of Pharmacology, 2010)
<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">Ethanolic extract of the roots of <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">C. spinarum<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> was evaluated for hepatoprotective and anti-oxidant activities in rats. Oral pre-treatment with ethanolic extract (100, 200 and 400 mg/kg) showed significant hepatoprotective activity against CCl<span style="font-size: 5.9939pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">4<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> and paracetamol-induced hepatotoxicity by decreasing the activities of bilirubin and lipid peroxidation, and significant increase in the levels of uric acid, glutathione, super oxide dismutase, catalase and protein in a dose dependent manner, which was confirmed by the decrease in liver wet weight and histopathological examination. The extract possessed strong anti-oxidant activity. This suggests that the hepatoprotective activity of <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">C. spinarum<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> is possibly attributed to its free radical scavenging properties.